2013
DOI: 10.1371/journal.pone.0066542
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the Cardiac Ryanodine Receptor Pore-Forming Region

Abstract: Ryanodine receptors are homotetrameric intracellular calcium release channels. The efficiency of these channels is underpinned by exceptional rates of cation translocation through the open channel and this is achieved at the expense of the high degree of selectivity characteristic of many other types of channel. Crystallization of prokaryotic potassium channels has provided insights into the structures and mechanisms responsible for ion selection and movement in these channels, however no equivalent structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The channel remains stable for at least 210 ns, and maintains a pore capable of ion transfer. In agreement with a recent study (61), in absence of its large cytoplasmic component, the RyR1 transmembrane domain in MD simulations can be stable on its own. The selectivity filter remains stable, and exposes, into the pore, the oxygen atoms required to substitute the ion solvation shell.…”
Section: Discussionsupporting
confidence: 93%
“…The channel remains stable for at least 210 ns, and maintains a pore capable of ion transfer. In agreement with a recent study (61), in absence of its large cytoplasmic component, the RyR1 transmembrane domain in MD simulations can be stable on its own. The selectivity filter remains stable, and exposes, into the pore, the oxygen atoms required to substitute the ion solvation shell.…”
Section: Discussionsupporting
confidence: 93%
“…Dilation of the pore does not occur via bending of S6 at a single ‘hinge’ alone, but rather by bowing and distortion of the S6 helix from a point midway through the membrane (Figure 4B), near the position of G4934 hinge, previously identified to influence gating of both RyR1 and RyR2 (Euden et al, 2013; Mei et al, 2015). Three other notable changes occur in the transmembrane region coincident with pore dilation.…”
Section: Resultsmentioning
confidence: 83%
“…Construction of a RyR1-Δ183-4006 deletion mutant and C-terminal construct of 1,377 amino acid residues showed that the RyR1 C-terminal portion forms a monovalent conducting channel activated by Ca 2+ and modified by ryanodine ( Bhat et al, 1997 ). The two C-terminal transmembrane segments that included the pore helix and connecting loops formed a homotetrameric assembly that conducted K + and Ca 2+ and also Cl, which suggests the loss of a cation-specific pathway ( Euden et al, 2013b ).…”
Section: Ryrs Are High-conductance Cation-selective Channelsmentioning
confidence: 99%